Potential of Spring Stover Harvest to Mitigate Stover Removal Impacts. Issue 1 (1st December 2013) - Houser, Christian D.; Roth, Greg W.; Beyer, David M.
Abstract : Demand for corn ( Zea mays L.) stover for biofuel production and feed and animal bedding and in Pennsylvania as a substrate for mushroom ( Agaricus bisporus ) production has been increasing. Harvesting stover in the spring and the fall was evaluated for 2 yr in Pennsylvania to estimate the impacts on the yield, nutrient content, and nutrient removal for the two harvest times. Stover yields in the spring (5342 lb/acre) averaged 2021 lb/acre or 27% less than fall stover yields (7363 lb/acre). Stover yields in the spring relative to the fall ranged from 59 to 89% indicating that overwinter conditions can impact spring stover yields. The nutrient concentration in the stover was generally similar from fall to spring, except that potassium concentrations declined from 0.74 to 0.30%, respectively, which indicates that nearly 60% of the potassium leached back into the soil. Lower potassium levels resulted in K2 O removal rates per ton to be reduced from 18.0 to 7.2 lb. At current fertilizer prices, this reduced nutrient removal costs from US12.26 to 5.92/ton. Although yields may be reduced, spring stover harvest could be a tactic to reduce the potential for erosion and runoff, reduce nutrient removal, and minimize some residue management issues with the next crop.